Pengelolaan Linen di Puskesmas Lubuk Basung Kabupaten Agam - R. Firwandri Marza; Deharnita Deharnita; Syaliati Syaliati (Poltekkes Kemenkes Padang, 2019)
Dirty linen is an important source of contamination at the health center. Although the linen is not used directly in the treatment process but its effect can be seen when handling linen not properly managed will lead to disease transmission is through nosocomial infections. The purpose of research is to know the description of washes and linen management processes in PHC Lubuk Basung Agam. The research method is descriptive qualitative approach, because this approach could explore deeply about the picture of the management of linen in Public Health Center of Lubuk Basung that is based on research objectives and principles - the principle of conformity (appropriateness) and sufficiency (adequacy). The total of research informants is sixpeople with in-depth interviews. The results show the different stages of the process of washing dirty linen weight (infectious) are soaked before input into the washing machine but do not use hot water, while the soiled linen mild (non-infectious) was not done soaking, for the washing process using one unit of washing machines and at the same stage should be stored in a closet storage for all kinds of linen in the health center. It is suggested for washing linen officers to pay more attention in the management of soiled linen weight (infectious). Soaking should use hot water and should always use personal protective equipments (PPE) in progress.